A method for preparing a high-entropy alloy electrocatalyst by anodic oxidation and microbial corrosion

By combining anodic oxidation with SRB microbial corrosion, a porous structure and FeS catalytic layer are constructed on the surface of high-entropy alloys, solving the problem of insufficient specific surface area of ​​bulk high-entropy alloy catalysts, improving catalytic performance, and achieving efficient OER reactions.

CN123043533APending Publication Date: 2026-11-06XIANGTAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611203252.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

In existing technologies, bulk high-entropy alloys have low specific surface area and insufficient exposure of active sites. The degree of modification by single SRB microbial corrosion is limited, making it difficult to significantly increase the specific surface area and sulfide generation, thus inhibiting the improvement of catalytic performance.

Method used

A porous structure was constructed on the surface of a high-entropy alloy by anodic oxidation pretreatment, and a FeS-rich catalytic layer was generated in situ by SRB microbial corrosion. Through the synergistic effect of structural regulation and composition optimization, the catalytic performance was significantly improved.

Benefits of technology

It significantly increases the metal-solution interface area, enhances the electron exchange process, improves the OER performance of the catalyst, and is suitable for large-scale preparation and industrial application due to its mild conditions and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123043533A_ABST
    Figure CN123043533A_ABST
Patent Text Reader

Abstract

This invention discloses a method for preparing an electrocatalyst for the oxygen evolution reaction (OER) of Al0.6CrFe2Ni2 high-entropy alloy using anodic oxidation combined with microbial corrosion, belonging to the field of electrochemical catalysis technology. The invention first pre-treats the bulk Al0.6CrFe2Ni2 high-entropy alloy with constant current anodic oxidation, generating a transition metal oxide layer with certain electrocatalytic activity on its surface. During the subsequent sulfate-reducing bacterial corrosion process, microbial metabolism sulfides the oxide layer, forming oxide-sulfide composite inclusions or heterojunctions, thereby enhancing catalytic performance through interfacial synergistic effects. Compared with existing technologies, this invention is the first to use anodic oxidation combined with microbial corrosion to improve catalytic performance, with mild preparation conditions and potential application prospects. It provides a new technical route for preparing other high-performance high-entropy alloy electrocatalysts using microbial corrosion engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical catalysis technology, specifically relating to a method for preparing a highly efficient high-entropy alloy oxygen evolution reaction electrocatalyst for water electrolysis through anodic oxidation pretreatment combined with microbial corrosion. Background Technology

[0002] Hydrogen, with its advantages of being clean and pollution-free, having high energy density, and being recyclable, is widely recognized as an ideal green secondary energy source and a core direction for future energy technology revolution and industrial development. Hydrogen production through water electrolysis can absorb surplus green electricity and achieve near-zero carbon emissions, making it the most promising green hydrogen supply method. However, the oxygen evolution reaction (OER) at the anolyte of water electrolysis is a four-electron transfer process with slow reaction kinetics. Therefore, using highly efficient electrocatalysts to reduce overpotential and improve reaction efficiency is crucial for hydrogen production through water electrolysis.

[0003] High-entropy alloys, composed of multiple main metals, can enrich catalytic active sites and optimize intermediate adsorption energies through high-entropy effects, lattice distortion effects, and multi-element synergistic effects, making them highly promising OER catalytic materials. However, bulk high-entropy alloys have low specific surface areas and insufficient exposure of active sites, limiting their intrinsic catalytic performance, which requires further improvement through surface modification.

[0004] Microbial corrosion is a common phenomenon in nature. Sulfate-reducing bacteria (SRBs), under anaerobic conditions, can utilize metallic iron as an electron donor to metabolize and generate H2S, which then reacts with metal ions to form FeS. Studies have confirmed that iron-based sulfides such as FeS possess excellent OER catalytic activity, thus a catalytic layer can be constructed in situ on the metal surface through SRB corrosion. This method is mild, low-cost, and aligns with the principles of green synthesis. However, the surface modification effect of SRB microbial corrosion on bulk high-entropy alloys is limited, making it difficult to significantly increase the specific surface area and resulting in insufficient sulfide formation, which inhibits further improvement in catalytic performance.

[0005] Anodizing is a simple and efficient metal surface modification technique that can selectively corrode the active phase of a material through constant current polarization, constructing cracks and porous structures on the surface, significantly increasing the reaction area, and providing more active sites for subsequent reactions. Currently, there are no reports on the synergistic application of anodizing and SRB microbial corrosion in the preparation of bulk high-entropy alloy OER electrocatalysts. Summary of the Invention

[0006] This invention addresses the limitation in performance improvement of bulk high-entropy alloy catalysts prepared by single SRB microbial corrosion, and provides a method for preparing Al through anodic oxidation combined with microbial corrosion. 0.6A method for developing a CrFe2Ni2 high-entropy alloy electrocatalyst. First, a porous structure is constructed on the alloy surface through anodic oxidation. Then, an in-situ FeS-rich catalytic layer is generated by SRB microbial corrosion. Through the synergistic effect of structural regulation and composition optimization, the OER performance of the catalyst is significantly improved.

[0007] The preparation method includes the following steps:

[0008] Step 1: Polish the Al 0.6 The CrFe2Ni2 high-entropy alloy underwent anodizing pretreatment, wherein the Al 0.6 CrFe2Ni2 high-entropy alloy can be purchased from the market or smelted by oneself according to metallurgical experience, without special requirements;

[0009] Step 2: Pre-culture the SRB bacteria in ATCC 1249 medium for several generations. It is recommended to purchase the SRB bacteria from the China General Microbiological Culture Collection Center. The recommended SRB bacteria is Desulfovibriovulgaris with the number CGMCC 1.5190. The composition and preparation method of the ATCC 1249 medium are publicly available.

[0010] Step 3: The alloy after anodizing pretreatment is placed in ATCC 1249 medium containing SRB for anaerobic immersion corrosion;

[0011] Step 4: Remove the alloy from the culture medium, clean and dry it to obtain the high-entropy alloy electrocatalyst.

[0012] The beneficial effects of this invention are as follows:

[0013] 1. This invention is the first to combine anodic oxidation pretreatment with SRB microbial corrosion for the preparation of bulk high-entropy alloy electrocatalysts. Anodizing selectively corrodes the active phase in the alloy, forming abundant cracks and pores on the surface: on the one hand, mass transfer is restricted within the pores, forming local anaerobic zones, which is beneficial to the metabolic activity of SRB anaerobic bacteria, enabling them to rapidly form biofilms and continuously metabolize within the pores; on the other hand, the pores significantly increase the metal-solution interface area, providing more reaction sites for the extracellular electron transfer of SRB, accelerating the electron exchange process between the microorganisms and the metal substrate, thereby enhancing the efficiency of SRB corrosion.

[0014] 2. The anodizing and microbial corrosion processes of this invention are carried out at room temperature and pressure, under mild conditions. Only conventional laboratory electrochemical equipment and culture equipment are required, without the need for harsh conditions such as high temperature and high pressure. The operation is simple and the parameters are controllable. The reagents used are inexpensive and readily available, and the overall preparation cost is low, making it suitable for large-scale preparation and industrial application.

[0015] 3. The optimal catalyst prepared by the method of this invention (600 mA·cm⁻¹) -2 Excellent performance (SRB corrosion after 5 days following 30 min of anodizing): In 1 MKOH alkaline electrolyte, 10 mA·cm⁻¹ -2 The OER overpotential at current density is only 314 mV, and the Tafel slope is as low as 47 mV·dec. −1 The charge transfer resistance is only 3.2 Ω; it can operate stably for 20 h at a potential of 1.544 V vs. RHE without significant performance degradation, and its catalytic activity and stability are significantly better than those of catalysts prepared by single SRB corrosion. Attached Figure Description

[0016] Figure 1 The images show surface SEM images of the catalysts prepared by synergistic SRB corrosion with different anodic oxidation parameters and the single SRB corrosion catalyst of the present invention; where (a) is the single SRB corrosion sample (SRB), (b) is the SRB-400-15 sample, (c) is the SRB-600-15 sample, (d) is the SRB-800-15 sample, (e) is the SRB-600-5 sample, and (f) is the SRB-600-30 sample.

[0017] Figure 2 XPS images of the optimal catalyst of this invention and a single SRB corrosion catalyst are shown; where (a) is the full spectrum, (b) is the high-resolution O 1s spectrum, (c) is the high-resolution S 2p spectrum, and (d) is the high-resolution Fe 2p spectrum.

[0018] Figure 3 The figures show the electrochemical performance of different catalysts of this invention; where (a) is the linear sweep voltammetry (LSV) curve, and (b) is the 10 mA·cm² curve. -2 The overpotential comparison diagrams at current densities are shown in (c) and (d) respectively. (c) is the Tafel slope fitting curve and (d) is the electrochemical impedance spectroscopy (Nyquist plot).

[0019] Figure 4 The following are stability test results for the optimal catalyst of this invention; where (a) is the chronocurrent test curve and (b) is a comparison of LSV curves before and after the stability test. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0021] Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this invention.

[0022] Unless otherwise specified, the experimental methods described in the following embodiments are conventional methods; unless otherwise specified, the reagents and materials are commercially available.

[0023] 1. Comparative Example 1: Preparation of high-entropy alloy catalyst by single SRB corrosion

[0024] Take a 600 mL anaerobic bottle, add 495 mL of sterilized and deoxygenated ATCC 1249 culture medium, then inoculate with 5 mL of third-generation SRB bacterial solution, place the polished high-entropy alloy sample in the bottle, seal with a rubber stopper, purge with high-purity nitrogen for 15 min for deoxygenation, and place in a constant temperature incubator at 30±2℃ for anaerobic soaking for 5 days. After soaking, remove the sample, immerse it in 5.0 wt.% glutaraldehyde solution for fixation for 5 h, then dehydrate it stepwise with 20%, 50%, 80%, and 100% ethanol for 20 min each, and finally dry it with nitrogen to obtain a catalyst sample for single SRB corrosion.

[0025] 2. Example 1: Preparation of catalyst by synergistic SRB corrosion with different anodic oxidation current densities

[0026] This embodiment investigates the effect of anodic oxidation current density on catalyst performance. The oxidation time is fixed at 15 min, and values ​​of 400, 600, and 800 mA·cm are set. -2 Three sets of current density parameters. Al 0.6 After grinding, polishing, and drying, the CrFe2Ni2 high-entropy alloy was subjected to anodic oxidation pretreatment using a three-electrode constant current polarization system. The high-entropy alloy was used as the working electrode, platinum foil as the counter electrode, and a saturated calomel electrode as the reference electrode. The electrolyte was a 3.5 wt.% NaCl solution, and the polarization was carried out at 400, 600, and 800 mA·cm⁻¹. -2 Constant current polarization was performed at the specified current density for 15 min. After oxidation, the sample was gently rinsed three times with deionized water to remove residual electrolytes on the surface, dried with nitrogen, and then placed in an anaerobic glove box for later use. Subsequent SRB cultivation, immersion corrosion, and post-treatment steps were exactly the same as those in Comparative Example 1, resulting in three groups of catalyst samples prepared at different current densities, designated as SRB-400-15, SRB-600-15, and SRB-800-15, respectively.

[0027] SEM characterization results showed that, compared with the single SRB corrosion sample of Comparative Example 1, the surface corrosion products of the sample pretreated with anodic oxidation were significantly increased, and a large number of cracks and pore structures appeared. EDS analysis showed that after anodic oxidation, the Al content of the sample surface underwent selective dissolution and decreased significantly, while the S content increased significantly, indicating that anodic oxidation promoted the formation of sulfides during SRB corrosion. Electrochemical performance test results showed that the three groups of samples at 10 mA·cm⁻¹... -2 The OER overpotentials at current densities were 323, 321, and 321 mV, respectively, and the Tafel slopes were 55, 53, and 53 mV·dec, respectively. -1 The charge transfer resistances were 3.7, 3.5, and 3.7 Ω, respectively, and the overall performance was better than that of Comparative Example 1; among them, the 600 mA·cm -2 The sample prepared at the current density has the best overall performance.

[0028] 3. Example 2: Preparation of catalyst by synergistic SRB corrosion with different anodizing times

[0029] This embodiment investigates the effect of anodic oxidation time on catalyst performance, with the current density fixed at 600 mA·cm⁻¹. -2 Three oxidation time parameters were set: 5, 15, and 30 min. All other operations and conditions were the same as in Example 1, except that the oxidation time was adjusted to 5, 15, and 30 min, respectively. Finally, three catalyst samples prepared with different oxidation times were obtained and were named SRB-600-5, SRB-600-15, and SRB-600-30, respectively.

[0030] Morphological characterization results showed that with prolonged oxidation time, the number of pores and cracks on the sample surface gradually increased, the corrosion product layer gradually thickened, and the product agglomeration phenomenon was obvious on the surface of SRB-600-30 sample, reaching the maximum specific surface area. XPS characterization results showed that compared with Comparative Example 1, the intensity of the S²⁻ characteristic peak in the S2p spectrum of SRB-600-30 sample was significantly enhanced, the proportion of the FeS corresponding peak in the Fe2p spectrum was significantly increased, and the metal oxide signal in the O1s spectrum was weakened, confirming that anodic oxidation pretreatment can significantly promote the sulfidation of subsequent SRB corrosion and generate more FeS with high catalytic activity. Electrochemical performance test results showed that the three groups of samples at 10 mA·cm⁻¹ exhibited good performance. -2 The OER overpotentials at current densities were 320, 321, and 314 mV, respectively, and the Tafel slopes were 49, 53, and 47 mV·dec, respectively. -1 The charge transfer resistances were 3.7, 3.5, and 3.2 Ω, respectively. Among them, the SRB-600-30 sample with an oxidation time of 30 min showed the best performance, the lowest overpotential, the fastest reaction kinetics, and the lowest charge transfer resistance.

[0031] 4. Example 3: Electrochemical performance and stability test of the optimal catalyst

[0032] The SRB-600-30 sample with the best performance in Example 2 was selected for system electrochemical performance testing. A standard three-electrode system was used in a 1 MkOH alkaline electrolyte at room temperature. The catalyst sample was used as the working electrode, the platinum sheet electrode as the counter electrode, and the Hg / HgO electrode as the reference electrode. All potentials were calculated using the formula...

[0033]

[0034] It is converted to a reversible hydrogen electrode potential.

[0035] Linear sweep voltammetry at 2 mV·s -1 The scan rate was determined. The results showed that the optimal catalyst sample had the lowest overpotential, at 314 mV; it also exhibited the lowest Tafel slope (47 mV·dec). -1 This indicates that it has faster OER reaction kinetics; its R ct The Ω value was also the smallest, at 3.2 Ω, exhibiting good catalytic performance. The optimal sample was subjected to a 20-hour long-term stability test using the chronoamperometry method at a constant potential of 1.544 V vs. RHE. The results showed that the sample current density remained stable overall without significant decay; the linear sweep voltammetric curves before and after the test almost overlapped, showing no significant degradation. This indicates that the catalyst prepared in this invention has excellent long-term operational stability and can meet the practical application requirements for hydrogen production via water electrolysis.

[0036] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing high-entropy alloy electrocatalysts through anodic oxidation combined with microbial corrosion, characterized in that, Includes the following steps: Step 1: Polish the Al 0.6 CrFe2Ni2 high-entropy alloy undergoes anodic oxidation pretreatment; Step 2: Pre-culture sulfate-reducing bacteria (SRB) in ATCC 1249 medium for several generations; Step 3: Immerse the pre-anodized alloy in ATCC 1249 medium containing SRB for anaerobic corrosion. Step 4: After soaking, remove the alloy, clean and dry it to obtain the high-entropy alloy electrocatalyst.

2. The preparation method according to claim 1, characterized in that, The anodizing current density is 400~800 mA·cm. -2 The oxidation time was 5-30 min. The SRB strain was *Desulfovibrio vulgaris* (*D. vulgaris*, CGMCC1.5190), cultured in ATCC 1249 medium. The SRB soaking time was 5 days. The catalytic performance of the prepared high-entropy alloy catalyst is as follows: in 1 MKOH alkaline electrolyte, 10 mA·cm⁻¹ -2 The OER overpotential at current density is only 314 mV, and the Tafel slope is as low as 47 mV·dec. −1 The charge transfer resistance is only 3.2 Ω; it can operate stably for 20 h at a potential of 1.544 V vs. RHE without significant performance degradation, and its catalytic activity and stability are significantly better than those of catalysts prepared by single SRB corrosion.